Estimating the return to endogenous schooling decisions for Australian workers via conditional second moments - Roger Klein; Francis Vella (Institute for the Study of Labor (IZA), 2006)
This paper employs conditional second moments to identify the impact of education in wage regressions where education is treated as endogenous. This approach avoids the use of instrumental variables in a setting where instruments are frequently not available. We employ this methodology to estimate the returns to schooling for a sample of Australian workers. We find that accounting for the endogeneity of education in this manner increases the estimated return to education from 6 percent to 10 percent.
urn:nbn:de:101:1-2009031324
Keywords: 330; Bildungsertrag; Regression; Instrumentalvariablen-Schätzmethode; Australien